Evaluation of suitability areas for ecotourism using multi-criteria analysis - Radmila Jovanovic; Fernando Almeida García; Rafael Cortés-Macías (European Journal of Geography)
Tourism in the wine region of Central Serbia has been gaining more and more affirmation in recent years. This wine destination offers to tourists a rich wine culture and recreation. Also, as a special supplement to wine tourism, ecotourism is especially promoted, in combination with quality wines with geographical origin. The basic analysis of this study is to identify potential locations for ecotourism activities in the wine region of Central Serbia based on physical-geographical elements (topography, altitude, slope, land use / coverage, diversity, distance from rivers) and socio-economic data (proximity to tourist attractions, distance from major roads and places). The integration of the Geographic Information System (GIS) and the Analytical Hierarchy Process (AHP) greatly facilitates the decision-making process in the assessment of ecotourism activities. As a result of this paper, a map of benefits for the development of ecotourism potentials was highlighted. Very high potential is shown by forest areas that can play a key role in tourism but are not fully used. This analysis helps in two ways: the promotion of ecotourism and viticultural destinations. In particular, in the assessment and implementation for local communities to identify tourism as an opportunity for economic development.